Study Between Public Sector Life Insurance and Private Sector Life Insurance: Exploring the Potential of India's Insurance Sector (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The Insurance sector plays a vital role in the economic development ofour nation. It acts as a mobiliser of savings, financial intermediary, promoterof investment activities, stabilizer of financial markets and a risk manager.India is still an under-insured country in the world. It is at the 18thposition among Life Insurance markets and 28th in Non-Life Insurance markets inthe world. This indicates that there is a huge potential, yet to be explored.